Drug safety: focus on long-term therapy with proton pump inhibitors. Possible cardiovascular risk and rare side effects - Dmitry I. Trukhan (LLC "MEDIAFORMAT", 2024)
Proton pump inhibitors are the most effective drugs for the treatment of acid-related diseases. In recent decades, the use of PPIs has increased exponentially. For a long time, PPIs were considered completely safe drugs for both short-term and long-term use. However, modern clinical guidelines note that when prescribing PPIs in large doses for a long period, the possibility of side effects should be taken into account. There are no reviews in the domestic literature on the safety of PPIs during long-term use. In this regard, a search was conducted in the PubMed and Scopus information databases for publications on the safety of PPI use, including sources up to November 15, 2023, which showed that long-term use of PPIs is associated with the possible development of numerous side effects. The first publications examined the likely side effects of long-term use of PPIs: the development of infections, increased risk of fractures and kidney pathology, and possible side effects: the risk of cancer and electrolyte disturbances. This review examines the possible cardiovascular risk of long-term PPI use and a number of rare side effects, many of which have been described in recent years. The key to mitigating side effects is judicious use of PPIs at the lowest effective dose and as quickly as possible. If there are clear indications for long-term PPI use, monitoring should be carried out to identify side effects.